Wave runup on smooth and rough slope of coastal structures / Ruzi Md Zain - Md Zain, Ruzi (1993)
Knowledge of wave runup levels is important for a proper design of the coastal structure especially breakwaters. An overall view of the literature, support the assertion that smooth slopes causes the highest possible runup levels.